Human Resources Recruitment and Selection Practices in Nigerian Organisations - Adeyoriju Rotimi; Fajebe Folorunso (Interdisciplinary Journal of Education, 2018)
This study examined human resources recruitment and selection practices in Nigerian organizations. To achieve this, literature were reviewed on recruitment and selection practices, current trends on recruitment and selection in Nigeria workplace, challenges and consequences of poor recruitment and selection practices, along with strategies for managing recruitment and selection in the Nigerian workplace. This study utilized Resource Based View and Equity Theory in order to build a solid argument for the discourse. Hence, this study concluded that recruiting right calibre of employee in the right position is sine qua non to organizational success. It is recommended that organizations in Nigeria should constantly ensure proper validity of recruitment and selection criteria in-line with global best practices so as to have a round peg in a round hole.